DETERMINAN FIRM VALUE : FINANCIAL PERFORMANCE SEBAGAI VARIABEL MODERATING - Barbara Gunawan; Jihan Mawarni (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2021)
This study aims to test the influence of Corporate Social Responsibility and Good Corporate Governance on Firm Value with Financial Performance as a Moderating Variable. The object of this research is a manufacturing company of consumer goods sector listed on the Indonesia Stock Exchange in 2016-2019 which amounts to 26 companies. This research uses sampling technique that is using purposive sampling method. The analysis tool used is Multiple Linear Regression and Moderated Regression Analysis (MRA) using SPSS 21 software. The results of this study showed that Corporate Social Responsibility has no effect on firm value, Corporate Governance which is proxed with institutional ownership negatively affects the firm value, Corporate Governance which is proxied with managerial ownership has a positive effect on the firm value, Corporate Governance which is proxy with the remuneration committee has no effect on the firm value, Financial Performance which is proxies by ROA is not able to strengthen the influence of Corporate social responsibility on firm value.